An Empirical Analysis of Exchange Rate Pass-Through to Prices in South Africa (2002-2016) - Maduku, Harris; Kaseeram, Irrshad (Journal of Economics and Behavioral Studies, 2018)
South Africa is currently running inflation targeting monetary policy since the year 2000 solely to achieve price stability. However, the persistent depreciation of the rand is making keeping inflation within the stipulated band very cumbersome. The objective of this paper is to find the duration taken by price indices to respond to exchange rate fluctuations. A Recursive VAR was used to investigate exchange rate passthrough (ERPT) to tradable prices in South Africa. Using monthly data, we find producer prices contributing highly to inflation with an average of 22% of fluctuations passed to prices. Large and persistent ERPT, especially on import and producer prices accompanied by high wage demands and a depreciating currency, are worrying factors for South Africa. Policy makers are advised to consider targeting the exchange rate if inflation is to be kept under control